Analisis Kualitas Pelayanan Room Attendant Terhadap Kepuasan Pelanggan Di Hotel Taman Simalem Resort - Silalahi, Andhre Vhibrian (Tourism, Hospitality And Culture Insights Journal, 2023)
This research was conducted using the interview method with the Room Attendant Supervisor by submitting several questions related to the Room Attendant service quality so as to obtain several responses from the parties interviewed by the researcher. This study aims to find out how the service system provided by the room attendant on customer satisfaction, which is where researchers come directly to conduct interviews with people who have been determined. The object of this research is Hotel Taman Simalem Resort. This re-search concludes that: Room Attendant Hotel Taman Simalem Resort Always tries to pro- vide satisfactory service for guests by following predetermined SOP customer